Sensors for Air Quality Monitoring (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Novel sensors to detect air pollutants like fine dust (PM10, PM2.5), O3, NO2, NO, or CO, as well as greenhouse gases like CO2, are currently available and have been widely used for atmospheric and indoor air monitoring. Although these sensors are small, lightweight, fast, and cheap, they can be relatively unstable and inaccurate. To address these limitations, further research is needed in the following areas: possibilities and shortcomings of new sensing techniques and applications; methodologies to overcome their disadvantages; solutions to integrate networks of these sensors into existing, well-calibrated air quality monitoring networks; solutions to use them for air quality monitoring; and their application in new tasks such as the detection of air pollution hot spots or the evaluation of emission inventories and numerical air pollution simulations. Environmental scientists, including physicians, chemists, and epidemiologists, play a vital role in defining the requirements for developing new sensors to detect harmful compounds in the atmosphere. The detection of personal air pollution exposure, and potentially personal pollen and fungi exposure in the future, is close to being elucidated and will form the basis for enhanced measures to improve human health.